2012
DOI: 10.5152/akd.2012.070
|View full text |Cite
|
Sign up to set email alerts
|

Does the surgical technique used in the orthotopic heart transplant affect the results regarding the rhythm

Abstract: Objective: The aim of this study was to compare the requirement for temporary and permanent pacemaker insertion and the incidence of the problems regarding the rhythm following heart transplantation with the bicaval or biatrial technique in the early postoperative period. Methods: Sixty-one patients underwent orthotopic heart transplantation between the dates of September 1989 and December 2008 in our clinics were included to the study. The study was designed as retrospective analysis, and all data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The initial standard technique for HTX, also known as the biatrial technique, has been associated with elevated rates of PPM implantation due to a continuous circular suture of the right donor and recipient atrium with possible sinus node injury (2,4,(8)(9)(10). In contrast, the bicaval technique uses two donor-to-recipient vena cava anastomoses preserving the right atrial (RA) integrity and the sinus node (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…The initial standard technique for HTX, also known as the biatrial technique, has been associated with elevated rates of PPM implantation due to a continuous circular suture of the right donor and recipient atrium with possible sinus node injury (2,4,(8)(9)(10). In contrast, the bicaval technique uses two donor-to-recipient vena cava anastomoses preserving the right atrial (RA) integrity and the sinus node (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive incision lines applied to atrial tissue may create electrophysiological instability by disturbing action potential propagation velocity and homogeneous distribution, thus creating a tendency to AF after using the biatrial technique. Owing to more extensive surgery lines, a temporary pacemaker requirement, left bundle branch block, and atrioventricular block were also observed statistically more significantly often compared to bicaval anastomosis [43] , [44] , [45] , [46] . In a study comparing the atrial arrhythmia incidence after both techniques, 31 bicaval and 35 biatrial operated patients were examined and the AF incidence were found to be significantly higher in the biatrial group (21 vs. 3 patients, p <0.01) [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, another modification of the bicaval technique has been given by Kitamura et al 5 Kara et al also reported, in a short postoperative followup analysis, lower rate of mitral or tricuspid valvular regurgitation and permanent pacemaker implantation by using bicaval technique compared with biatrial technique. 12 Another modification of the bicaval technique to reduce tricuspid valve regurgitation by modifying inferior vena caval anastomosis presented by Marelli et al also focuses on the influence of RA anterior wall stress through traditional bicaval technique. 6 Our modified RA anastomosis (cavoatrial technique) can be apprehended as a combination of the two traditional techniques.…”
Section: Discussionmentioning
confidence: 99%